Determinants of Corporate Social Responsibility Disclosure in Indonesia - Bela Sulistyaguna; Yuli Chomsatu Samrotun; Endang Masitoh Wahyuningsih (Universitas Pamulang, 2021)
ABSTRACTCorporate social responsibility is the company’s obligation to the stakeholders to be seen as a responsible business entity. The purpose of this research was to analyze the influence of company size, company age, industry type, liquidity, profitability, leverage, board of directors, board of commissioners, audit committee, and public ownership on the corporate social responsibility disclosure. Analysis of data using multiple linear regression method with SPSS 22.0 for mac. The sample consists of companies listed on the Indonesia Stock Exchange (IDX) and disclosed the Global Reporting Initiative (GRI) sustainability reports from 2013 to 2018. The final sample of this research was 18 companies that obtained by purposive sampling. The results of the research showed that, simultaneously, company size, company age, industry type, liquidity, profitability, leverage, board of directors, board of commissioners, audit committee, and public ownership have an influence on the corporate social responsibility disclosure. Partially, the results showed that liquidity and leverage have an influence on corporate social responsibility disclosure. Meanwhile, company size, company age, industry type, profitability, board of director, board of commissioner, audit committee, and public ownership has no influence on corporate social responsibility disclosure